B2B E-Commerce Adoption and Competitive Advantage: Insights from SMEs in East Java - Munawaroh, Nuril Aulia; Ambarwati, Diana; Ramadhan, Tri Sugiarti; Putra, Yudiarto Perdana (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2025)
The rapid advancement of digital technology has encouraged small and medium-sized enterprises (SMEs) to adopt business-to-business (B2B) e-commerce as a strategic tool to enhance their competitive advantage. However, the level of B2B e-commerce adoption among SMEs varies, influenced by technological, organizational, and environmental factors. This study examines the impact of B2B e-commerce adoption on SMEs in East Java, focusing on its role in improving cost efficiency, differentiation, growth, and product quality. The research employs a quantitative approach, surveying SMEs engaged in manufacturing and affiliated with industry associations. The findings reveal that relative advantage, top management support, firm size, business partner pressure, and government support significantly influence the adoption of higher levels of B2B e-commerce. Furthermore, a higher level of adoption is positively correlated with improved competitive advantage, particularly in facilitating business expansion and increasing market reach. The results highlight the need for policymakers and business stakeholders to support SMEs in adopting advanced e-commerce solutions. This study contributes to the existing literature by demonstrating the staged adoption of B2B e-commerce and its direct and indirect effects on SME competitiveness.